2022
DOI: 10.1186/s12879-022-07696-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of humoral immune response over 17 months of COVID-19 pandemic in a large cohort of healthcare workers in Spain: the ProHEpiC-19 study

Abstract: Background Understanding the immune response to the SARS-CoV-2 virus is critical for efficient monitoring and control strategies. The ProHEpic-19 cohort provides a fine-grained description of the kinetics of antibodies after SARS-CoV-2 infection with an exceptional resolution over 17 months. Methods We established a cohort of 769 healthcare workers including healthy and infected with SARS-CoV-2 in northern Barcelona to determine the kinetics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The seroprevalence of IgG antibodies against SARS-CoV-2 varied according to the study population and geographic region. We reported a seroprevalence of 42.69% of anti-N IgG antibodies; similar studies have reported a seroprevalence from 16.9% to 41.7% [14,17,18], associated with the constant exposition of health workers to COVID-19 patients and asymptomatic infections. In our studied population, patients reported obesity, hypertension, and diabetes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The seroprevalence of IgG antibodies against SARS-CoV-2 varied according to the study population and geographic region. We reported a seroprevalence of 42.69% of anti-N IgG antibodies; similar studies have reported a seroprevalence from 16.9% to 41.7% [14,17,18], associated with the constant exposition of health workers to COVID-19 patients and asymptomatic infections. In our studied population, patients reported obesity, hypertension, and diabetes.…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of IgG antibodies against the N protein varied according to the geographic region, disease severity, group, and occupational exposition [13][14][15]; specifically in health workers, the reported prevalence went from 4.14% to 41.7% [14,[16][17][18]. Health workers had a higher risk of infection due to direct contact with infected patients and the development of asymptomatic disease [19].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-N and anti-S antibodies detected with the ECLIA method have been reported to persist at 9 months in ≥ 90% of subjects who were infected by COVID-19 [11]. Additionally, a recent study conducted in Spain (the ProHEpiC-19 cohort study) demonstrated the persistence of positive anti-N antibodies until 450 days (15 months) [21].…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor in influencing the SARS-CoV2 level at 6 months was the peak antibody level following the second vaccination of the primary vaccine regimen. Studies examining the antibody decay kinetics in participants following COVID-19 infection showed that the height of the peak is dependent on disease severity with antibodies for IgG remaining above the positivity threshold for up to 500 days 15–17. Following vaccination our study showed that SARS-CoV2-Ig Ab persistence (≥7.0 U/mL) was 62 days for the AZ and 210 days for the Pfizer vaccine.…”
Section: Discussionmentioning
confidence: 60%